Life on the front line : diaries, news and letters from the First World War, 1914-1919. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2012)
This collection contains an assortment of letters and journals from British soldiers and military men during the First World War. As such, the material offers an absorbing, and often tragic, account of what life was like for British soldiers in the trenches. The subject matter includes descriptions of the long and intimidating journey to the front, of combat including shelling and trench battles, as well as of discussions of morale, discipline, and mental health. The files cover the crucial and infamous battles of the Somme and Ypres, as well as the battles of Loos, Arras, Vimy Ridge, and Bethune. The volumes are divided into military rank from Privates to General-Brigadiers, demonstrating how the experience of warfare differed depending on your position within the British military. Furthermore, the collection contains diaries of those combatants captured by Central Power forces and offers a detailed look into the experience of prisoners of war from Germany to Turkey. The collection also contains non-combatant experiences of the First World War in the form of the diaries of a chaplain and French civilian living close to the frontline. Overall, the material gives a engrossing and heartbreaking account of the first-hand experience of World War One.
Date range: 1914-1919.
Keywords: World War, 1914-1918 -- Personal narratives, British; Great Britain -- History -- 20th century